2019
DOI: 10.3390/ijerph16183280
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Multilevel Factors Related to Urban Community Trust in Healthcare and Research

Abstract: Background: Community and patient engagement in the healthcare system and biomedical research are prerequisites for eliminating health disparities. We conducted a “listening tour” to enhance our understanding of multilevel factors associated with community trust. Methods: Using community-based participatory research (CBPR) methods, we conducted a phenomenological qualitative study. “Town-hall” style discussions were held at nine sites across an urban, Midwestern city. We recruited adults (N = 130) via communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 24 publications
3
46
0
Order By: Relevance
“…The second way that allocating by death rates achieves benefits that would be lost by prioritizing other communities is that the communities in which death rates are the highest are the same communities that have long histories of disparities wrought by, among other thigs, mistreatment and mistrust (Webb Hooper et al 2019). Prioritizing these communities can help repair this trust.…”
Section: Criteria For Allocationmentioning
confidence: 99%
“…The second way that allocating by death rates achieves benefits that would be lost by prioritizing other communities is that the communities in which death rates are the highest are the same communities that have long histories of disparities wrought by, among other thigs, mistreatment and mistrust (Webb Hooper et al 2019). Prioritizing these communities can help repair this trust.…”
Section: Criteria For Allocationmentioning
confidence: 99%
“…Medical research on African Americans (AAs) has a fraught history that has resulted in limited knowledge of racial differences in various pathologies, as well as an understandable hesitance for minorities to participate in research ( Hooper et al, 2019 ). Several studies addressing racial disparities in Alzheimer disease (AD) and stroke have found higher incidence rates in the Black population for both diseases as compared with the non-Hispanic white (NHW) population ( Benjamin et al, 2017 , Manly and Mayeux, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of health care, competence means possessing resources and knowledge, and feeling capable of taking the steps required to maintain one’s health. Autonomy refers to the choice to pursue specific health goals rather than feeling pressured to follow a doctor’s orders or by an already distrusted medical establishment [ 15 ]. Relatedness in the healthcare environment means feeling supported by health care professionals and by peers.…”
Section: Introductionmentioning
confidence: 99%